Mahāda yethe jhālelyā 15 vyā Bauddha Sāhitya Sammela-nātīla sammelanādhyaksha Śrī. Bhāūsāheba Aḍasūḷa yāñce adhyakshīya bhāshaṇa - Aḍasūḷa, Bhāūsāheba, 1933- (Mahārāshṭra Bauddha Sāhitya Parishada, 1977)
On the plight of untouchables in India; presidential address of the author at the 15th Bauddha Sāhitya Sammelana, Mahad, Kolaba District, 1977.